Novel defected ground structure and two-side loading scheme for miniaturized dual-band SIW bandpass filter designs - Xu, Shanshan (2015)
This letter reports a novel back-to-back E-shaped defected ground structure (DGS) and two-side loading scheme for miniaturized dual-band substrate integrated waveguide (SIW) bandpass filter (BPF) designs. The SIW loaded by novel DGS supports evanescent-mode wave propagation below the cut-off frequency of SIW, while achieves two transmission poles at the passband and two controllable transmission zero points. Furthermore, the novel loading scheme by loading different-sized DGS resonators on two sides of SIW is proposed for dual-band BPF designs. To validate the design and analysis, a 2.4/5.2 GHz filter prototype was designed. In good agreement with theoretical results, the measured results of the dual-band filter achieve insertion losses of 3.6 and 3.1 dB, and fractional bandwidths of 5.8% and 6.45% at 2.4 and 5.2 GHz, respectively. The filter size is only 408 mil × 420 mil.